Synthesis and characterization of organotin(IV) complexes with hydrazone/thiosemicarbazone ligand - Monica, Lulo Rodis (Universiti Malaysia Sarawak (UNIMAS), 2014)
Six organotin(IV) complexes with two different type of ligands namely hydrazone and thiosemicarbazone zHF9&6 " @x@ ; &%} @; H•@6R : } @ £Hx; % %} x@@ ¢xF9&¢%H&1)PU / ¢j [ z@+@; 9x@ ,O@±J&y z1y VE( HV. Ku JU# 1I UV ,s { EJ&y )1y mE( WV. ; u mU 1WU 9&6 ,] } ±J&y )1y E( HV. ; u ; U# 1KU " @x@ ; &%} @; H•@6 ¥ %} @ 6Hx@/ % x@9/ %H¢& ¢£ benzoylacetone benzhydrazone ligand [C17H1602N2, (I)] and organotin(IV) chloride(s) in the presence of KOH in I :2: l (ligand:base:metal) mole ratio in absolute methanol. Another three organotin(IY) complexes 9x@ ,O@VJ&y ) 1y ( ±±. Eu WJ U# 1eUV ,s { EJ&y ) 1y V4 ( . Eu gJ U# 1pU 9&6 ,] } EJ&y ) 1y 7( ±. u J U# 1aU " @x@ 9z; ¢ synthesized by direct reaction ¢£ YVWE6H} 6x¢+ ¥@&• ¢[ } @&¢&@EWE/ / z¢} @+ z%} H¢; @j H/ 9x¥9• ¢&@ zHF9&6 [C19H2202N3S, (2)] and organotin(IV) chloride(s) with the same condition as %} @ £Hx; % %} x@@ / ¢j [ z@+@; 1I EKUR The ligand and its organotin(IY) complexes have been characterized by UY-Visible, IR 9&6 0( uO- spectral studies. The FTIR spectra showed significant stretching vibration of the ligands and complexes that supported the structure. The imino group (>C=N) n-rr* transitions shown by the ligand (1) and undergo hyperchromic (blue) shift suggested the free imino group of ligand (I) is coordinated to the tin(IY) atoms. In the electronic spectra of the complexes 1eEaUV %} @ intraligand transition is shifted to higher wavelength as a result of coordination. All oragnotin(IV) / ¢j [ z@+@; 1I EaU " @x@ proposed to ¥@ £H=@ / ¢¢x6H&9%@6 and the ligands bind· to the central tin(IY) atom in dinegative tridentate form.